Distribution network design: a literature review and a research agenda. Issue 5 (1st June 2015) - Mangiaracina, Riccardo; Song, Guang; Perego, Alessandro
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is threefold. First, it classifies research on distribution network design (DND) according to the methodologies adopted and themes tackled. Second, it discusses the main implications for practitioners. Finally, it proposes a few promising directions for future research. Design/methodology/approach – The review is based on 126 papers published from 1972 to 2013 in international peer-reviewed journals in the Business, Management and Economics field. The academic papers have been analyzed and classified based on the main research methods used and the themes tackled. Findings – It was found that most of the earlier research adopted quantitative models to deal with different decisions on DND, whereas the number of conceptual papers, proposing frameworks and classifications, is still limited. In all, 42 factors that affect DND have been identified and classified into five groups, and the relationships between factor groups and strategic decisions have been investigated. This study revealed that some important areas have not received much attention in the literature and, therefore, three potential directions for further research have been identified. Research limitations/implications – Due to the extremely large number of papers on DND, it is possible that a few papers may have inadvertently been missed. Despite the possibility of not being all-inclusive, the authors firmly believe that the general picture presented in this paper is precise and trustworthy. Originality/value – This review offers valuable insights for practitioners: a clear understanding of the main decisions related to DND; a comprehensive analysis of the main factors that affect the distribution network structure; a clear understanding of the relationships between factor groups and key decisions; and a guide to the models that can be used to support the different phases of DND.